ChemInform Abstract: Mollenynes B—E from the Marine Sponge Spirastrella mollis. Band‐Selective Heteronuclear Single Quantum Coherence for Discrimination of Bromo—Chloro Regioisomerism in Natural Products. Issue 10 (February 2016) - Wang, Xiao; Duggan, Brendan M.; Molinski, Tadeusz F.
Abstract: Four novel halogenated ene‐ynes, mollenynes B—E, are isolated in nanomole yields from the marine sponge Spirastrella mollis from the Hogsty Reef, Bahamas.